2014
DOI: 10.1108/ijdi-11-2013-0077
|View full text |Cite
|
Sign up to set email alerts
|

Organic coffee certification in Peru as an alternative development-oriented drug control policy

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm:448207 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Tey et al (2012) suggested based on their findings, the Malaysian vegetable sector has experienced a low adoption rate of sustainable agricultural practices and imply only a few farmers have adopted it. Further improvement on organic farming technology or organic production system is necessary in the future (Garcia, 2014). In this report, we can determine the acceptance (Murad et al, 2015) of sustainable farming technology among farmers.…”
Section: Sustainable Farming Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Tey et al (2012) suggested based on their findings, the Malaysian vegetable sector has experienced a low adoption rate of sustainable agricultural practices and imply only a few farmers have adopted it. Further improvement on organic farming technology or organic production system is necessary in the future (Garcia, 2014). In this report, we can determine the acceptance (Murad et al, 2015) of sustainable farming technology among farmers.…”
Section: Sustainable Farming Technologymentioning
confidence: 99%
“…Social influence is the degree to which a person feels that it is important for the others to believe that they also should implement the same system (Venkatesh et al, 2003). It is believed that farmers who have the availability of a big family member can be influenced in accepting sustainable farming technology (Garcia, 2014).…”
Section: Social Influencementioning
confidence: 99%
“…Therefore, considering the functional explanation of prevention as an important tool on the path to sustainable development; and considering that in order to deal with the criminals phenomenon must go to the underlying factors and its social origins and through their neutralization, eliminate or at least reduce the possibility of crime; and by understanding the fact that the issue of criminal confrontation may be only transient and responsive in the short-term, but permanently and in the long run perpetrators behavior will change and will emerge in new forms of crime; and that based on scientific facts, relying on punishment and intensifying criminal reactions, without considering the causes and contexts of crime, is considered as a kind of the struggle against the effects and in the word of realism it cannot have a significant impact, and therefore, paying attention to the pre-criminal stages is considered as necessary and inevitable (Garcia-Yi, 2014).…”
Section: Social Crime Prevention and Realistic Criminal Policymentioning
confidence: 99%
“…5 Other authors point to positive e ects of alternative development programs, emphasizing the key role of social development, poverty reduction and community-based activities to create social capital (Cohen, 2009;Dispanadda Diskul et al, 2019), as well as that of price premiums inherent to organic and fair-trade certified products (Garcia-Yi, 2014).…”
Section: Introductionmentioning
confidence: 99%